Impacto de la Nueva Cultura Laboral en el Sur de Tamaulipas - Cepeda Robledo, Dulce Alexandra; Ochoa García, Roberto; Casanova Varela, Basilio (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2008)
The present report analyzes the impact of the media campaigns that promote the New Labor’s Culture, implemented at federal level by the Bureau of Work, (STPS) of México; in order to know its effectiveness in South Tamaulipas, México, identifying the used mass media; studying the answer of enterprise organizations and unions in the adoption and diffusion of the attitudes, values and philosophy of the New Labor’s Culture; and observing the changes reflected in the worker – boss relationship. Methodologically is used an analysis of content of printed messages, and television’s broadcasted messages; also some interviews to the enterprise and union leaders of the services sector in the zone. These results reveal semiotic and logistic deficiencies that reduce the efficiency in the positive adoption of messages.
Keywords: New Labor culture; Advertising Campaign; Organizational Communication; Analysis of content; Mediatic perception